„Mneme” w „Dziejach” Herodota - Narecki, Krzysztof (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
The word mneme, “memory”, appears 16 times in the Histories of Herodotus. The author, using the philological analysis of all its occurrences, investigates not only its significance in specific contexts but also defines and names functions that the word has in its place of use. Finally, the author classifies the identified meanings of the word mneme (in combination with the accompanying verbs) and compares its functions (as defined by the context).